Transitional justice with a differential approach for indigenous peoples victims of the armed conflict: the Wiwa case of the Sierra Nevada de Santa Marta1 - Fonseca Lidueña, Carlos Milton (Contemporary justice review, 2025)
Based on the judicial and extrajudicial mechanisms of transitional justice adopted in Colombia, the research conducted with the Wiwa people reviews these mechanisms to guarantee their right(s) and to materialize collective ethnic justice in transitional justice. It is noted that the differential approach and affirmative measures aimed at promoting the rights to truth, justice, reparation and guarantee of non-repetition of minority groups such as Indigenous peoples have been implemented. In summary, this research aims to understand the scope of the conception of intercultural transitional justice and to identify the model of inter-justice in the relationship between ‘derecho propio’ (Indigenous law) and transitional restorative justice.